Effect of Inpatient Physiotherapy Reconditioning Program on Pain, Functional Mobility and Spinal Muscle Performance in Prolonged Bedridden Patients : A Comparative Study - Shinde, Dr. Sandeep; Misal, Poonam; Aphale, Sawani R. (South Eastern European Journal of Public Health, 2025)
Background: Immobilization for prolonged duration can cause severe complications. The study evaluates the impact of reconditioning program on pain levels, functional mobility and spinal muscle performance in prolonged bedridden patients.Objective: The study aimed to evaluate the impact of a reconditioning program on pain, functional mobility and spinal muscle performance in patients with immobilization for long time.Methods: The study included one hundred and six participants of 35-55 age group with lower limb injuries, such as fractures of the femur, tibia, and fibula. Subjects were randomly assigned to either a conventional treatment group (Group A) or an experimental exercise program group (Group B). Both groups underwent treatment for four weeks, and data analysis utilized a paired t-test for within group analysis and unpaired t-test for between group analysis.Results: Both groups A and B showed significant difference in all the three outcome measures but group B showed extremely significant improvement (<0.0001) in the outcome measures taken i.e. pain, lumbar strength by manual muscle testing, functional mobility by Functional Independence Measure Scale than group A. Conclusion: Both conventional and experimental reconditioning programs effectively enhanced muscle strength, functional mobility and reduced pain levels in prolonged bedridden patients. However, the experimental group (Group B) showed a more pronounced impact on pain reduction and improvement in lumbar flexor, rotator and extensor muscle strength, functional mobility compared to the conventional treatment group (Group A).